2006
DOI: 10.1002/app.24428
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of free volume, interfacial, and toughening behavior for cyanate ester/bentonite nanocomposites by positron annihilation

Abstract: Effects of filler on microstructure and toughening behavior of cyanate ester (CE)/bentonite (BT) nanocomposites with different content of BT have been studied by positron annihilation lifetime spectroscopy, X-ray diffraction, transmission electron microscopy, dynamic mechanical analysis, etc. The interesting results found by PALS indicate that the size and concentration of the free volume holes and the apparent free volume fraction increased with increasing the content of BT, which indicates that adding nano-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Previous researches have proved that the magnitude of the intermediate lifetime ( I 2 ) is related to the interfacial property in polymer hybrids, so the values of I 2 for cured CE resin and various hybrids were detected, and the corresponding data are shown in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…Previous researches have proved that the magnitude of the intermediate lifetime ( I 2 ) is related to the interfacial property in polymer hybrids, so the values of I 2 for cured CE resin and various hybrids were detected, and the corresponding data are shown in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al observed a decrease in T g by the addition of 1 wt% organically modified Bentonite into cyanate ester. However, 2 wt% Bentonite added system has T g comparable to that of the neat resin [30]. Earlier studies on nanoclay (K-10) incorporated epoxy syntactic foams showed improvement in storage modulus and T g by the addition of 1 and 2 wt% nanoclay.…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 86%
“…It was similar with the results observed in other polymer nanocomposites. [25][26][27] Nanoparticles have very large specific surface area and surface activity. More interfacial layers would form between the uniformly dispersed nanoparticles and polymer matrix.…”
Section: Free Volume Properties Of the Compositesmentioning
confidence: 99%